Farmácia clínica e atenção farmacêutica: estratégias de apoio à farmacoterapia na pandemia de Covid-19 - Matos, Ariane Lopes de (Brasil, 2022)
Covid-19 is an infectious disease that has a high mortality rate caused by the new coronavirus identified as Sars-coV-2. Several studies have highlighted the importance of clinical pharmaceutical activities in the follow-up and guidance of patients in the community pharmacy; in solving drug-related problems (DRP) and in the effectiveness and/or adherence to pharmacotherapy in patients undergoing hospital medical follow-up. Thus, in the context of the covid-19 pandemic, where there is no 100% safe and effective treatment, drugs in off-label use, lack of information, and self-medication, the pharmacist plays a fundamental role in preventing errors and/or duplication of doses, therapeutic substitutions, monitoring of biological markers and detection of adverse reactions and/or drug interactions. Through the 10 selected scientific articles, it was found that both in the community pharmacy and in the hospital unit, pharmacists led the cases to a better clinical outcome.